Nature protection in Bosnia and Herzegovina: state and perspectives - Đug, Samir; Drešković, Nusret (Journal for Geography, 2012)
Bosnia and Herzegovina is distinguished by a very unique mosaic of high biodiversity level. However, current development activities and initiatives for construction of new dams, together with activities in the forestry sector throughout the country, emphasizes the need for establishment of new protected areas in all major ecosystem types that should be ecologically viable and effectively managed. A review of the history of protected areas and administration developments in Bosnia and Herzegovina provide useful input for analysis. However, the data on the current state and size of protected areas in the country are obsolate and inaccurate. The results of the analysis have shown that in spite of a very high biodiversity level, Bosnia and Herzegovina managed to designate only 2.6% of its territory as protected areas, which is far below regional and European level. Lack of protected areas system is one of the main direct threats to biodiversity conservation. The primary objective of establishment of protected area network (PAN) in Bosnia and Herzegovina is to ensure conservation of valuable natural areas, which contain representatives of all main ecosystem types that could be found in the country. Only in this way, sustainable conservation of biodiversity could be achieved.